Toward an inclusive digital health system for sexual and gender minorities in Canada. (4th October 2021) - Antonio, Marcy; Lau, Francis; Davison, Kelly; Devor, Aaron; Queen, Roz; Courtney, Karen
Abstract: Most digital health systems (DHS) are unable to capture gender, sex, and sexual orientation (GSSO) data beyond a single binary attribute with female and male options. This binary system discourages access to preventative screening and gender-affirming care for sexual and gender minority (SGM) people. We conducted this 1-year multi-method project and cocreated an action plan to modernize GSSO information practices in Canadian DHS. The proposed actions are to: (1) Envisage an equity- and SGM-oriented health system; (2) Engage communities and organizations to modernize GSSO information practices in DHS; (3) Establish an inclusive GSSO terminology; (4) Enable DHS to collect, use, exchange, and reuse standardized GSSO data; (5) Integrate GSSO data collection and use within organizations; (6) Educate staff to provide culturally competent care and inform patients on the need for GSSO data; and (7) Establish a central hub to coordinate efforts.